Α1‐antitrypsin Pittsburgh and plasmin‐mediated proteolysis. (2nd September 2016) - Henneuse, A.; Suchon, P.; Chambost, H.; Morange, P. E.; Frere, C.; Alessi, M. C.
Abstract : Essentials Patients with α‐1‐antitrypsin (α1‐AT) Pittsburgh exhibit a mild bleeding tendency. A new case of α1‐AT Pittsburgh with suspected high antifibrinolytic potential was studied. We showed that α1‐AT Pittsburgh inhibits tissue plasminogen activator and plasmin. The antifibrinolytic potential of the variant contributes to explaining the mild bleeding phenotype. Summary: α1 ‐Antitrypsin (α1 ‐AT) Pittsburgh has a Met358 to Arg substitution at the reactive Met–Ser site of α1 ‐AT, which enables the protein to act as a potent thrombin inhibitor. Four patients with α1 ‐AT Pittsburgh have been described to date. An additional young girl was recently diagnosed with α1 ‐AT Pittsburgh in our center after presenting with a large hematoma in the forearm. Interestingly, all of these patients showed a potent thrombin inhibitor in the plasma and a mild bleeding phenotype. This observation suggests that the in vivo consequences of the mutation may contribute to the maintenance of normal hemostatic balance. We assessed inhibition of the fibrinolytic system by the variant protein by evaluating the fibrinolysis inhibitory potential of the patient's plasma, purified wild‐type α1 ‐AT and purified Pittsburgh α1 ‐AT with an electrophoretic zymography system, western blotting, and clot fibrinolysis. Our results indicate that the patient's plasma and purified α1 ‐AT Pittsburgh have strong potential to inhibit tissue‐type plasminogen activator and plasmin.